A Triboelectric Self‐Powered Sensor for Tire Condition Monitoring: Concept, Design, Fabrication, and Experiments. Issue 12 (24th August 2017) - Askari, Hassan; Saadatnia, Zia; Khajepour, Amir; Khamesee, Mir Behrad; Zu, Jean
Abstract : This paper presents a novel type of triboelectric‐based self‐powered sensor for tire condition monitoring. The triboelectric based sensor is made of highly flexible, mechanically and thermally durable, and cost‐effective polymeric materials. The authors firstly report the location inside of a tire for attaching the sensor to monitor tire conditions. Then, the authors analyze the performance of the sensor under different frequencies and stroke displacements to show the capability of the fabricated device as a self‐powered sensor. Furthermore, the authors evaluate the durability and performance of the sensor to delineate its potential for tire condition monitoring. The results show that the fabricated self‐powered sensor has the potential of measuring the tire forces and pressure. The use of the proposed sensor for tire condition monitoring systems (TCMS) can be considered as a significant step toward developing smart tires, improving vehicles control strategy, and accordingly, enhancing passengers safety. Abstract : Triboelectric Nano Generator for Tire Condition Monitoring: As the figure shows, with attaching a new sensory device to a tire, we can obtain crucial information pertinent to its dynamics. The use of the proposed sensor for tire condition monitoring systems (TCMS) is a significant step toward developing smart tires, improving vehicles control strategy, and accordingly, enhancing passengers safety and reduction of disastrous accidents.